2020
DOI: 10.1186/s13229-020-00338-1
|View full text |Cite
|
Sign up to set email alerts
|

Inattention and hyperactive/impulsive component scores do not differentiate between autism spectrum disorder and attention-deficit/hyperactivity disorder in a clinical sample

Abstract: Background: Although there is high co-occurrence between ASD and ADHD, the nature of this co-occurrence remains unclear. Our study aimed to examine the underlying relationship between ASD and ADHD symptoms in a combined sample of children with a primary clinical diagnosis of ASD or ADHD. Methods: Participants included children and youth (aged 3-20 years) with a clinical diagnosis of ASD (n = 303) or ADHD (n = 319) for a total of 622 participants. Parents of these children completed the social communication que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 50 publications
(68 reference statements)
6
39
0
Order By: Relevance
“…As for impulsivity and hyperactivity, some participants considered those symptoms stemmed from ASD, and other participants considered ADHD. Previous research revealed that one group of children with diagnosed ASD and the other group of ADHD had similar impulsivity and hyperactivity scores, although ASD group showed significantly higher scores in social communication deficits and repetitive behaviours [35]. Participants' remarks based on clinical experiences might prove current research trends on ASD and ADHD's comorbidity.…”
Section: Discussionmentioning
confidence: 91%
“…As for impulsivity and hyperactivity, some participants considered those symptoms stemmed from ASD, and other participants considered ADHD. Previous research revealed that one group of children with diagnosed ASD and the other group of ADHD had similar impulsivity and hyperactivity scores, although ASD group showed significantly higher scores in social communication deficits and repetitive behaviours [35]. Participants' remarks based on clinical experiences might prove current research trends on ASD and ADHD's comorbidity.…”
Section: Discussionmentioning
confidence: 91%
“…A particular challenge to the use of these data for the identification of individuals with ASD is that ASD is one of a series of neurodevelopmental disorders (e.g., ADHD and OCD) that share common traits (Krakowski et al, 2020; Kushki et al, 2019; Taurines et al, 2012), and etiology (Cross‐Disorder Group of the Psychiatric Genomics Consortium, 2013; Faraone & Larsson, 2019; Gonzalez‐Mantilla, Moreno‐De‐Luca, Ledbetter, & Martin, 2016; Lowther et al, 2017; Zarrei et al, 2019), frequently co‐occurring within individuals (Lai et al, 2019). A recent meta‐analysis found that 28% of individuals with ASD also have ADHD and 9% have OCD (Lai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As for impulsivity and hyperactivity, some participants considered those symptoms stemmed from ASD, and other participants considered ADHD. Previous research revealed that one group of children with diagnosed ASD and the other group of ADHD had similar impulsivity and hyperactivity scores, although ASD group showed significantly higher scores in social communication deficits and repetitive behaviours [31]. Participants' remarks based on clinical experiences might prove current research trends on ASD and ADHD's comorbidity.…”
Section: Children With Dental Phobia Possibly Derived From Mental Heamentioning
confidence: 91%